Cino da Pistoia and the Book of Songs Written by Petrarca. Making a Book as a Text - Pavol Koprda (Slovenska Literatura, 2004)
The subject of the study is the Book of Songs written by Petrarca. It could be considered to be the first piece of modern literature. The starting point of creating the modern literature comes from the moment when a literary work stopped to be an expression of a fixed semantic hierarchy. In the period after the reign of the Hohenstauf family a new social climate arose in Italy, it was a social environment without clear hierarchy of values. The Bible was replaced by an encyclopedia, which became a directional book for the communal bourgeoisie. Equal values of any term are typical for a terminology in the encyclopedia. It is up to a reader to make structures and hierarchies of the terms by his own. A man, a reader, makes connections among terms, which do not look similar at all. Two dissimilar things look like similar ones, if a social community considers them both to be similar things, if the reconstructed scheme expresses a wide social experience. This social phenomenon has been being followed by literature. It is a matter of literature to find new codes, to join dissimilar things, to create a new net of similar ones, organized in a new hierarchic system. The literature has not already been a matter of elite. The study consists of three parts. An introduction deals with the beginning of micro-texts, poetic forms – stanzas, sonnets. They were the first forms making analogies of disjunctive things, joining together independent contents. The second part is dedicated to the Petrarca´s Book of Songs as the first macro-text of the first book in the world literature. It is difficult to step out from creating micro-text to macro-text. It requires from an author to create an individualized perception of time duration, to destroy an objective historical time and to replace it by subjective time as a story of “me”. It is important to make it in a way, adequate and believable to an audience. If this time transformation is successful, a literary work becomes a part of the literary process. A history of literature is also created on this basis. Petrarca learned an art of creating a fine macro-text from the works of Cino Da Pistola. The last part of my study deals with topois and hidden structures from the works of Cino Da Pistola, which became inspirations for Petrarca´s literary work.